Evidence on the Purchasing Power Parity in Panel of Cities - Tomas del Barrio; Josep Ll Carrion; Enrique Lopez-Bazo (European Regional Science Association (ERSA), 2003)
The power purchasing parity (PPP) hypothesis and the law of one price (LOP) predict (long-run) price equalization across the space. In the absence of market frictions and transport costs, arbitrage should guarantee the same price, in a common currency, for a given commodity in different locations. Contradictory evidence has been reported at the international level, though generally concluding large and persistent price deviations. In this paper we show that long-run price convergence cannot be rejected in a sample of Spanish cities over a long period of time, using newly developed non-stationary panel data techniques. Robust estimates show an important dispersion of half lives in the Spanish cities. The paper also includes the analysis of the causes behind price deviations across the sample of cities.
Keywords: 330